2022
DOI: 10.1101/2022.10.19.22281282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low perfusion and missed diagnosis of hypoxemia by pulse oximetry in darkly pigmented skin: A prospective study

Abstract: ImportanceRetrospective clinical trials of pulse oximeter accuracy report more frequent missed diagnoses of hypoxemia in hospitalized Black patients than White patients, differences that may contribute to racial disparities in health and health care. Retrospective studies have limitations including mistiming of blood samples and oximeter readings, inconsistent use of functional versus fractional saturation, and self-reported race used as a surrogate for skin color. Understanding the cause of biased readings by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Evaluation of skin tone only occurred in three studies. 18 , 19 , 20 The proportion of participants with darker skin tones or of non-White ethnicities was particularly low in earlier studies ( Supplementary Table S2 ). One study comprised 100% Black participants.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Evaluation of skin tone only occurred in three studies. 18 , 19 , 20 The proportion of participants with darker skin tones or of non-White ethnicities was particularly low in earlier studies ( Supplementary Table S2 ). One study comprised 100% Black participants.…”
Section: Resultsmentioning
confidence: 86%
“… 57 One of these three studies presented bias data and reported a consistent underestimation of true SaO 2 in a cohort of 33 Black participants with a maximum bias of –7.1 (9.0)%. 20 , 24 , 25 , 27 , 31 , 33 , 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that Black patients may be sicker when they are treated in intensive care units, and racial disparities in the delivery of critical care medicine may be contributing to the racial difference in the prevalence of occult hypoxemia. Notably, a recent study by Gudelunas et al suggested that low perfusion state is a significant contributor to the pulse oximetry errors when combined with darker skin pigmentation (21).…”
Section: Discussionmentioning
confidence: 99%
“…The studies above demonstrate that not only is there significant bias in measurement of oxygen saturation in individuals with darker skin tones, it also translates into poorer healthcare delivery and clinical outcomes for these patients, which further perpetuates health inequities. The literature also highlights that the magnitude of inaccuracy with different skin tones is variable and not well-quantified, differing by device and other patient factors, including low perfusion ( 49 , 58 ). These studies were all performed in HICs, and there is a critical paucity of such data in LMICs.…”
Section: Methodsmentioning
confidence: 99%
“…Bias in pulse oximetry measurements Pulse oximetry (SpO 2 ) does not perfectly correlate with arterial oxygen saturation (SaO 2 ) as measured by blood gas, and prior studies have found multiple potential sources of inaccuracy, particularly as patients become sicker, as denoted by rising lactate and hypoxia (48,49). These include severe hypoxemia, low perfusion, patient movement, and severe anemia.…”
Section: Context-specific Considerations In Lmicsmentioning
confidence: 99%